2018
DOI: 10.1097/der.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Baseline Patch Test Series: Pediatric Contact Dermatitis Workgroup

Abstract: A baseline pediatric patch test panel was established through working group consensus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…A meta‐analysis done found that studies published after 1995 have reported higher rates of positive patch tests 8,9 . In recent years, unique patch test series have been developed to facilitate diagnosis and management of ACD in children 8,10 . Our rates of sensitization and relevant positive patch tests are similar to other studies published in the past decade 8,11,12 …”
Section: Discussionsupporting
confidence: 61%
“…A meta‐analysis done found that studies published after 1995 have reported higher rates of positive patch tests 8,9 . In recent years, unique patch test series have been developed to facilitate diagnosis and management of ACD in children 8,10 . Our rates of sensitization and relevant positive patch tests are similar to other studies published in the past decade 8,11,12 …”
Section: Discussionsupporting
confidence: 61%
“…In addition, two of the most common allergens encountered in children with HE in this study (benzalkonium chloride, oleamidopropyl dimethylamine) and one of the allergens that was significantly increased in children with HE (2-mercaptobenzothiazole) are not present on the American Contact Dermatitis Society recommended paediatric screening series. 25 Most of the HE-associated allergens are commonly used in personal care products and topical medications. Methylisothiazolinone is an almost ubiquitous preservative used in leave-on and rinse-off personal care products, including shampoos, conditioners, moisturizers and nail polish, industrial chemicals, paint, slime, adhesive agents and even prescription medications.…”
Section: Discussionmentioning
confidence: 99%
“…An American survey of dermatologists and allergists conducting patch testing in children attending the 2017 American Contact Dermatitis Society meeting held in Washington, D.C., resulted in a discussion of collected data and a consensus review by a pediatric contact dermatitis working group at the conference. A baseline pediatric patch test panel for children above 6 years old was established through working group consensus children [150] and consists of 38 allergens: beside the allergens mentioned above, the following allergens were included: MI; formaldehyde releasers, i.e., quaternium-15, diazolidinyl urea, imidazolidinyl urea, DMDM hydantoin, bromonitropropanediol (bronopol), and iodopropynyl butylcarbamate; corticosteroids, i.e., tixocortol-21-pivalate, hydrocortisone-17butyrate, clobetasol-17-propionate, and budesonide; surfactants, i.e., cocamidopropyl betaine and its impurities dimethylaminopropylamine and amidoamine and emulsifiers, i.e., amerchol L101 and decyl glucoside; natural products, i.e., propolis, sesquiterpene lactone and Compositae mix, tea tree oil, cinnamic aldehyde, and carmine; bacitracin; propylene glycol; fragrance mix II; carba mix; and benzophenone-3.…”
Section: Is It Advisable To Test With a Shortened Standard Series Formentioning
confidence: 99%